Pengaruh Tekanan Anggaran Waktu Dan Fee Audit Terhadap Kualitas Audit Dimoderasi Kecerdasan Emosional - Hamzah Ahmad; Hajering Hajering; Muslim Muslim; Alma Pratiwi (Jurnal Widya Akuntansi dan Keuangan, 2020)
This study aims to examine the effect of time budget pressure and audit fees on audit quality with emotional intelligence as a moderating variable. The data in this study were obtained from BPKP South Sulawesi Province representatives who were willing to become respondents. This study uses primary data by conducting direct research in the field by giving questionnaires / question sheets to 112 respondents. The data analysis method uses the SmartPLS approach to examine the effect of time budget pressure and audit fees on audit quality with emotional intelligence as a moderating variable. The results showed that the time budget pressure variable had a negative and significant effect on audit quality; audit fees have a positive and not significant effect on audit quality; emotional intelligence can strengthen the relationship of time budget pressure to audit quality; and emotional intelligence cannot strengthen the audit fee relationship to audit quality